FAKTOR-FAKTOR YANG MEMENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KOTA TANGERANG - Aurelia Putri Hadi Atmaja; Rian Sumarta (E-Jurnal Akuntansi TSM, 2023)
This research aims to analyze and obtain empirical evidence on the factors that influence taxpayer compliance, such as the modern tax administration system, tax knowledge, tax service quality, tax socialization, attitude, awareness, and tax sanctions. This study uses the object of individual taxpayers in Tangerang City. The sample used in this study was 107 respondents with data collection by distributing questionnaires through Google Forms Link. This study uses purposive sampling and uses a 4-point Linkert Scale. This study provides results that the variables of modern tax administration systems, tax knowledge, tax socialization, attitude, awareness, and tax sanctions have an effect on taxpayer compliance. While the variables of tax service quality and attitude have no effect on taxpayer compliance. This indicates that the higher the implementation of the modern tax administration system, the level of knowledge, the implementation of tax socialization, the level of awareness, and the application of tax sanctions can increase taxpayer compliance.